2014
DOI: 10.1155/2014/246283
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Helminth Parasites Community of Fish Species in a Niger Delta Tidal Creek, Nigeria

Abstract: , at flood tides, were examined for gastrointestinal helminth parasites. The fish species were caught with hooks and lines and cast nets. Only nematode parasites were encountered in the study. Of the 1,149 fish specimens examined, 213 (representing 18.5%) were infected with various nematodes parasites. Dasyatis margarita had the highest prevalence rate of 66.7% (2 infected out of 3 examined), followed by Pseudotolithus (Pseudotolithus) senegalensis with a prevalence of 41.7% (10 infected out of 24), while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
5
3
Order By: Relevance
“…The parasite burden of the individual species however revealed a higher burden on B. africanus. The presence of only one family of nematode from this study, in both species of gobies from both sampling stations indicated low parasite species diversity which is not in agreement with the report by [18] on the Niger Delta tidal creek in Nigeria where they recorded no infestation in the gobies species collected from Buguma creek. The parasite Ascaris and Anisakis have been recorded from…”
Section: Discussioncontrasting
confidence: 99%
“…The parasite burden of the individual species however revealed a higher burden on B. africanus. The presence of only one family of nematode from this study, in both species of gobies from both sampling stations indicated low parasite species diversity which is not in agreement with the report by [18] on the Niger Delta tidal creek in Nigeria where they recorded no infestation in the gobies species collected from Buguma creek. The parasite Ascaris and Anisakis have been recorded from…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that the occurrence of parasitism varies from one habitat to another and it could be due to host-parasite relationship and abiotic factors. However, the species composition of the parasites found in both fish species in this study are fewer that other studies [2,13,18]. The small number of the parasite composition isolated in this study could be due to the fact that the composition of fish parasite fauna is influenced more decisively by the fish species composition and the relatively small numbers of fish examined.…”
Section: Discussioncontrasting
confidence: 78%
“…Pathological conditions resulting from parasites and diseases cause high magnitude of epidemics under crowded and other unnatural conditions [12]. The role of freshwater fish in transmitting parasites to humans had been known for a long time [2,13]. Zoonotic diseases that result from the ingestion of raw or undercooked fish include opisthorchiasis, diphyllobothriasis, clonorchiasis, gnathosomiasis, helminthiasis and anisakiasis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, highest parasitic infestation was observed in large size fish whereas Pandey et al (2012) reported highest parasitic infection in middle sized and lowers helminthes susceptibility in small and large size fishes. The reported overall prevalence of internal parasites of fish was 17.9% in Karachi Fish Harbour, 18.5% at Niger Delta Tidal Creek and 20.83% at Lake Ziway, respectively (Qasim and Ayub 2012, Ogbeibu et al 2014, Bekele and Hussien 2015. Difference in prevalence of parasites in fishes may be due to the feeding habits of the host fish, population density, their life span, moving through various habitats, change in the environmental conditions and body size (Berra 2001).…”
Section: Resultsmentioning
confidence: 99%